PENDAMPINGAN PEMANFAATAN LIMBAH PADAT PRODUK PERIKANAN DI TPI SODOHOA SEBAGAI PUPUK ORGANIK - Rosmawati, R; Bubun, Rita L; Assiddieq, Mochammad (Universitas Muhammadiyah Parepare, 2020)
The Sodohoa fish auction site is an area with high levels of daily pollution in the city of Kendari. So far, the activities of fish buying and selling businesses have not shown any effort to control the problems caused by the almost daily production of fishery product waste. This problem becomes the focal point for problem solving that will be carried out in the Community Partnership Program assistance. The aim of this activity is to increase community knowledge and skills through the use of fishery processing waste into organic fertilizer thereby improving the use value and economic value of the waste. Program implementation began with discussion activities with partner groups and local communities involved in fish buying and selling activities at the Sodohoa Fish Auction Place through discussion group forums. The methods used to solve partner group problems are (1) counseling and improving skills in processing fishery waste into organic fertilizer, (2) coaching and mentoring, and (3) dissemination and trials of the use of organic fertilizer. The Pabalu Balu partner group has been able to make organic fertilizer using a simple method from waste raw materials in the form of offal which is often found at TPI Sodohoa and has been trialled with the Subur Makmur partner group, with the hope that they can switch to using organic fertilizer made from fishery waste instead of artificial fertilizers. they have often used it so far.